How Can the Crisis Vulnerability of Emerging Economies Be Reduced? - Klaus Abberger; Biswa Nath Bhattacharyay; Chang Woon Nam; Gernot Nerb; Siegfried Schoenherr (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2014)
Emerging countries in many cases are more crisis-prone than highly developed industrialized countries. This is in many cases due to a weak or volatile financial sector. The best policy to strengthen crisis resistance is the building up of a sound financial position. A sound financial position of a country also increases the capacities to get out of a crisis. For getting out of a crisis, however, an important additional general condition must be fulfilled: the economy must increase its international competitiveness to assure growth, the only way out of a crisis. Building up a sound financial position and a competitive private sector, therefore, should be a pre-crisis policy. It relates to the public sector as well as the financial institutions. Once a crisis has erupted in an unsound financial environment there is no chance to escape a crisis sustainably avoiding a painful process. The blueprint for getting out of a crisis suggests a complex policy approach. The private financial sector must undergo structural reforms (in reality closing down or downscaling unsound institutions) and the government must apply fiscal austerity measures to reduce public debt, regaining credibility and by this creating new fiscal options for counteracting crisis effects. Labour costs can be reduced by increasing the labour market flexibility (e.g. by easier hiring and firing and higher wage spreads especially towards the lower wage scale) and by measures directly reducing labour costs. The result of such measures will be an increase of unemployment and of felt unemployment risks by large population groups as well as general real income losses from labour. The fiscal austerity measures in addition and in short term will reduce economic activities and thus aggravate the social problems. These negative social effects of getting out of a crisis are the most crucial and controversial policy issue. People and their interest organizations to a greatly varying extent will accept or refuse.
Keywords: E44; E61; F32; F33; F34; F42; G01; H63; O57; 330; Wirtschaftskrise; Prävention; Krisenmanagement; Wirtschaftspolitik; Schwellenländer; Wirtschaftskrise; Wirtschaftspolitik; Wirtschaftliche Anpassung; Stabilisierungspolitik; Frühwarnsystem; Schuldenkrise; Schwellenländer; Südkorea; Mexiko; Systemtransformation; Estland